Kontribusi Persatuan Tarbiyah Islamiyah (PERTI) dalam Pembaruan dan Pelestarian Pendidikan Islam - Zain, Najmal Hadi; Iswantir, Iswantir (Universitas Pahlawan Tuanku Tambusai, 2024)
As a religion rahmatan lil'alamin, Islam has many aspects in the form of education, rituals and theology. Islamic mass organizations were established to meet the religious needs of humanity including in the field of education. This study aims to identify the role of the PERTI mass organization in the renewal and preservation of Islamic education. The research method uses the library research method. Persatuan Tarbiyah Islamiyah (PERTI) is one of the organizations in the field of social religion and Islamic education. It emerged in the background of the development of religious understanding changing the pattern of education which was initially in the form of a surau then changed into a more modern madrasah but still maintained the essentials of Islamic boarding schools such as sciences oriented towards tafaqquh fi al-din by studying the yellow book. These sciences are required to be motivated by faith in Allah so that a sincere nature arises because of Allah alone, not for the world.